The mixed metric dimension of flower snarks and wheels - Danas Milica Milivojević (De Gruyter, 2021)
New graph invariant, which is called a mixed metric dimension, has been recently introduced. In this paper, exact results of the mixed metric dimension on two special classes of graphs are found: flower snarks JnJ_{n} and wheels WnW_{n}. It is proved that the mixed metric dimension for J5J_{5} is equal to 5, while for higher dimensions it is constant and equal to 4. For WnW_{n}, the mixed metric dimension is not constant, but it is equal to nn when n≥4n\ge 4, while it is equal to 4, for n=3n=3.